Retracted: Curcumin ameliorates atherosclerosis through upregulation of miR‐126. Issue 11 (23rd April 2019) - Li, Yezhou; Tian, Leilei; Sun, Dajun; Yin, Dexin
Abstract: The potential usage of curcumin in diverse human diseases has been widely studied, including arteriosclerosis (AS). This study focused on investigating the relationship between curcumin and AS‐associated microRNA, which may provide a better understanding of curcumin in a different mechanism. Human microvascular endothelial HMEC‐1 cells were treated by curcumin alone or oxidized low‐density lipoprotein (ox‐LDL) plus curcumin, after which the following parameters were analyzed: cell viability, migration, and the expression of AS‐associated factors. The regulatory effects of curcumin on miR‐126 and signaling pathways involved in AS were then studied. Further, an animal model of AS was stimulated by feeding rabbits with 1% cholesterol diet. The effects of curcumin on the animal model were explored. We found that curcumin treatment significantly reduced HMEC‐1 cells viability, migration, and the protein levels of MMP‐2, MMP‐9, and vascular endothelial growth factor (VEGF) in the presence or absence of ox‐LDL. Meanwhile, the expression of VEGFR1 and VEGFR2 was repressed by curcumin. miR‐126 was upregulated by curcumin. The abovementioned effects of curcumin on HMEC‐1 cells were all attenuated when miR‐126 was silenced. And also, VEGF was a target gene of miR‐126, and curcumin could inhibit the activation of PI3K/AKT JAK2/STAT5 signaling pathways via miR‐126. The effects of curcumin and its regulation on miR‐126 and VEGF were confirmed in the animal model of AS. To sum up, curcumin exerted potent anti‐AS property possibly via upregulating miR‐126 and thereby inhibiting PI3K/AKT and JAK2/STAT5 signaling pathways. Abstract : To sum up, curcumin exerted potent antiarteriosclerosis property possibly via upregulating miR‐126 and thereby inhibiting PI3K/AKT and JAK2/STAT5 signaling pathways.